Diagnosis of Indian visceral leishmaniasis by nucleic acid detection using PCR. - Pankaj Srivastava; Sanjana Mehrotra; Puja Tiwary; Jaya Chakravarty; Shyam Sundar (PLoS ONE, 2011)
PCR based diagnosis for Visceral Leishmaniasis (VL), despite numerous published primers, remains far from being applied in the field. The present study was planned to design a Leishmania specific diagnostic assay and to evaluate its sensitivity and specificity on a sample size, which to the best of our knowledge is the largest ever screened in one study.Leishmania specific primers were developed using 18S rRNA gene and their sensitivity was evaluated on 500 parasitologically confirmed patients with VL and 25 Post Kala-azar Dermal Leishmaniasis (PKDL) patients. Specificity was calculated on 250 healthy endemic controls, 250 healthy non endemic controls and 250 non leishmanial diseases like malaria.Our PCR assay had a sensitivity of 87.8% (95%CI: 84.1-89.8) using 200 µL of patient's peripheral-blood. Specificity was absolute in non-endemic healthy controls and in subjects with different diseases while in endemic controls it was 84% (95%CI: 78.9-88.0). Its overall specificity was 94.6% (95%CI-92.8-96.1).The PCR assay developed is sensitive enough to detect the 18S rRNA gene in an amount equivalent to a single parasite or less in a one million human cell environment. The high sensitivity of this PCR diagnostic test with relatively non-invasive peripheral blood sampling method opens up the possibility of its deployment in field for the routine diagnosis of VL.